Low prevalence of hepatitis delta infection in Cuban HBsAg carriers: Prospect for elimination - de los Ángeles Rodríguez Lay, Licel; Tan, Zexi; Villalba, Maria Caridad Montalvo; Suárez, Marcia Samada; Corredor, Marité Bello; Hernández, Dayesi López; Sánchez, Barbara Marrero; Alonso, Lidunka Valdés; Sausy, Aurélie; Hübschen, Judith M. (Frontiers in Medicine, 2023)
Infection with hepatitis delta virus (HDV) is one of the most severe hepatitis B virus (HBV) complications, with a more rapid progression to cirrhosis and an increased risk of hepatic decompensation and death. Data on HDV infection in Cuba is limited. The aims of our study were to determine the HDV prevalence in HBsAg carriers and to characterize the HDV strains circulating. The data were used to assess the possibility of HDV elimination in the Cuban HBV epidemiological setting. Five hundred and two serum samples from the same number of HBsAg carriers collected in the period 2006 - 2019 from all over the country were tested for anti-HDV total antibodies. If positive, the samples were analyzed for HDV-RNA using Real Time RT-PCR targeting the ribozyme and HD antigen domains followed by genotyping based on phylogenetic analysis. Two samples were anti-HDV positive (0.39% [95% CI 0.11-1.44]). One of them was also HDV-RNA positive. Clinically the patient with active HDV infection had compensated liver cirrhosis. Phylogenetic analysis showed that the virus belonged to genotype 1 and thus clustered with contemporary strains from North America, Europe, Middle East and Asia. This is the first HDV study, including molecular detection and virus characterization, done after the introduction of the universal childhood anti-hepatitis B vaccination. The very low prevalence of HDV infection in HBsAg carriers combined with the high HBV vaccination coverage of all newborn children, of previously identified risk groups, and of the general population currently under 40 years of age, suggest that HDV elimination is feasible in Cuba if the success in HBV control is maintained.